2017
DOI: 10.1248/cpb.c17-00425
|View full text |Cite
|
Sign up to set email alerts
|

Gibbs Free Energy of Hydrolytic Water Molecule in Acyl-Enzyme Intermediates of a Serine Protease: A Potential Application for Computer-Aided Discovery of Mechanism-Based Reversible Covalent Inhibitors

Abstract: In order to predict the potencies of mechanism-based reversible covalent inhibitors, the relationships between calculated Gibbs free energy of hydrolytic water molecule in acyl-trypsin intermediates and experimentally measured catalytic rate constants (k) were investigated. After obtaining representative solution structures by molecular dynamics (MD) simulations, hydration thermodynamics analyses using WaterMap™ were conducted. Consequently, we found for the first time that when Gibbs free energy of the hydrol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 18 publications
0
1
0
Order By: Relevance
“…For estimation of the reaction rates, quantum mechanics calculations have revealed the energetics and kinetics of enzymes. [8][9][10] We recently reported that hydration thermodynamics analysis could be a useful method for estimating the catalytic rate constants of the serine protease trypsin. 11) Hydration thermodynamics analysis can predict the locations for hydration on protein surfaces and the relative energies at the locations with simple procedures and reasonable computational time.…”
mentioning
confidence: 99%
“…For estimation of the reaction rates, quantum mechanics calculations have revealed the energetics and kinetics of enzymes. [8][9][10] We recently reported that hydration thermodynamics analysis could be a useful method for estimating the catalytic rate constants of the serine protease trypsin. 11) Hydration thermodynamics analysis can predict the locations for hydration on protein surfaces and the relative energies at the locations with simple procedures and reasonable computational time.…”
mentioning
confidence: 99%